Effect of Job Satisfaction, Compensation, Organizational Commitment and Profestic Leadership Style on Turnover Intention - Agustin, Nadilla Triasih; Samekto, Agus (JEMBA: Journal of Economics, Management, Business and Accounting, 2023)
The era of globalization, many employees are competing fiercely for seats in existing large companies. However, not a few are also willing to leave and move from one company to another for various reasons. The purpose of this study is to determine the effect of job satisfaction on turnover intention, the effect of compensation on turnover intention, the effect of organizational commitment on turnover intention, and the influence of prophetic leadership style on turnover intention. The method used is a quantitative method with data collection, namely distributing questionnaires to employees of PT. Pysil Lasibe Kasanea. The data were analyzed using WarpPLS 7.0. The results in this study indicate that job satisfaction has a positive effect on turnover intention, compensation has a positive effect on turnover intention, organizational commitment has a positive effect on turnover intention and prophetic leadership style has a positive effect on turnover intention.